2020
DOI: 10.1111/jmi.12936
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy as an imaging tool to study the bio/nonbio complexes

Abstract: Atomic force microscopy (AFM) besides X-ray crystallography and electron microscopy is one of the most attractive methods to study bio/nonbio complexes. Information on how biomacromolecules interact with nanomaterials under different environmental conditions has important implications for the practice of nanomedicine and concerning the safety of nanomaterials. These complexes cover a broad range both in terms of stability and composition. AFM offers a wealth of structural and functional data about such assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The deposition of CS on the surface of PP‐g‐PAA made the film smoother, as indicated by the range of Ra and image Z (Figure 3g). In addition to analyzing the surface through AFM, surface roughness can also be quantified by measuring the average roughness and root mean square of the AFM (Bednarikova et al., 2020). Studies on the grafting of poly(ethylene glycol) onto PA membrane composites have shown, through AFM analysis, that the surface morphology of the membrane changed due to the formation of the top poly(ethylene glycol) grafting layer.…”
Section: Characterization Of Grafted Polymersmentioning
confidence: 99%
“…The deposition of CS on the surface of PP‐g‐PAA made the film smoother, as indicated by the range of Ra and image Z (Figure 3g). In addition to analyzing the surface through AFM, surface roughness can also be quantified by measuring the average roughness and root mean square of the AFM (Bednarikova et al., 2020). Studies on the grafting of poly(ethylene glycol) onto PA membrane composites have shown, through AFM analysis, that the surface morphology of the membrane changed due to the formation of the top poly(ethylene glycol) grafting layer.…”
Section: Characterization Of Grafted Polymersmentioning
confidence: 99%
“…In the last decades, Atomic Force Microscopy (AFM) has become a common tool to study biological materials ( Bednarikova et al, 2020 ), ( Piontek and Roos, 2018 ), ( Dufrêne et al, 2017 ). Scanning probe microscopes, the family of instruments to which AFM belongs, were developed in the eighties, primarily as surface characterization instruments in solid material science ( Binnig and Rohrer, 1999 ).…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…In addition, it was presented a phenomenological and simple model to follow the evolution of the surface of thin films during their growth under nonstochastic deposition conditions on substrates characterised by high roughness, with the capability of reproducing synthetic depositions of different films and experimental contexts. 3 Bednarikova et al 2 reviewed several advancement in scanning probe techniques for biological applications, for example for the investigation of proteins, lipids and DNA, and also larger objects such as cells. A detailed application of atomic force microscopy for the variation of the mechanical properties of red blood cells (erythrocytes) due to spur cell anaemia and cold agglutinated disease is reported, aiming to develop erythrocyte-based mechanical biomarkers, useful for disease diagnosis and therapy monitoring.…”
mentioning
confidence: 99%
“…Bednarikova et al 2 . reviewed several advancement in scanning probe techniques for biological applications, for example for the investigation of proteins, lipids and DNA, and also larger objects such as cells.…”
mentioning
confidence: 99%